Street food Design in Public Space Gunung Sari Indah Surabaya - Rizka Tiara Maharani (Warta Pengabdian, 2022)
The development of Gunung Sari Indah as a new neighborhood creates an impetus for increased housing and street food. Street food vendors set up shop on strategic roads to sell their products, causing crowds and traffic jams that disrupt the comfort. As a result, the focus of this research is on how to design street food in public spaces. This research uses the questioner, interview, and field survey methods. The questionnaire and interview are held to learn about the seller's aspirations for layout setting and facilities that they expect. A field survey is required to learn about the existing conditions, such as road width, seller position, and products offered. Furthermore, the issue of COVID-19 should be considered to avoid the virus spreading in public places. As a result, the layout setting should be aware of new normal health protocols such as physical distancing, handwashing, and environmental hygiene. The street food layout setting will be formed by a color box mural with an area of one car parking lot 2.5 m x 5 m for one seller, resulting in a gap. Then, the East Road, which closes in the evening, will be the focus of street food. Nonetheless, signage is required for traffic management in order to reduce traffic congestion and provide comfort to visitors to this area.